The potential of NZEB for existing and prospective school buildings by applying energy conservation measures and efficient technologies suitable for hot arid climate - Almutairi, Hamad H.; Almutairi, Jaber H.; Alhashem, Abdulwahab E.; Almutairi, Abdulrahman S. (Frontiers in Energy Research, 2024)
This work attempts to resolve the challenges associated with shifting school buildings to NZEB in Kuwait. A systematic approach is suggested that is focused on two scenarios for new and retrofitted schools. This approach covers several energy conservation measures with the help of DesignBuilder Building Thermal Simulation, and it examines different scenarios to utilize 80% of the area of the roof for the installation of Photovoltaics (PV) and on-site wind turbines. Both types of schools have similar renewable energy capacities, but the new school can utilize all of the suggested energy conservation measures. The superiority of the design of the new school will result in an annual saving of 770 MWh of electricity rather than the 462 MWh that will be provided the retrofitted school. The economic assessment indicates that utilizing the highest roof area for PV installations fulfils the NZEB balance, with respective discounted paybacks of 3.55 and 5.54 years for the new and retrofitted schools. However, adding wind turbines was found to be less practical due to a longer breakeven period compared to rooftop PV alone. The estimated annual savings are 589 GWh for the existing 1,275 schools under the retrofitting scheme and 130 GWh for 170 new schools, whereas operating PV at 80% of the area of the roof for each school can generate 40.63 GWh in 25 years and avoid the production of 29.23 kilotons of CO2.